The effects of relaxation techniques following acute, high intensity football training on parasympathetic reactivation - Renaghan, Eric; Wishon, Michael Joseph; Wittels, Harrison L.; Feigenbaum, Luis A.; Bellamy, Kyle; Hatfield, Michael; Girardi, Joe; Lee, Stephen; McDonald, Samantha M.; Wittels, S. Howard (Frontiers in Sports and Active Living, 2023)
Purpose: To evaluate the impact of mindfulness and rest activities on PNS reactivation following training sessions, in a sample of Division-I collegiate, male football athletes. Methods: This study employed a cross-sectional, pre-post experimental design among 38 football athletes. Following three training sessions, each separated by one week, athletes were exposed to three groups: mindfulness, rest, and no-intervention. Athletes in the mindfulness group laid supine in a darkened room, while performing 15 minutes of guided breathing and body scans. The rest group remained seated in a lighted room, performing 15 minutes of restful activities (e.g., talking). The no-intervention group was instructed to perform usual post-training activities (e.g., showering). Heart rate (HR), respiration rate (RR) and two HR variability (HRV) indices were measured via an armband monitor (Warfighter Monitor, Tiger Tech Solutions, Inc, Miami, FL) equipped with electrocardiographic and photoplethysmography capabilities. HRV indices included standard deviation of the N-N intervals (SDNN) and root mean square of successive RR interval differences (rMSSD). Within and between-group differences were determined via analysis of variance (ANOVA). Results: Statistically significant reductions in HR and RR were observed across all groups: -81.6, -66.4, -40.9 bpm and -31.7, -26.9, and -19.0 breaths⋅min-1, respectively. The mindfulness and rest groups exhibited a larger within-group reduction in HR and RR compared to the no-intervention group, p<0.0000. Additionally, the mindfulness group showed a larger reduction in HR and RR compared to the rest group, p<0.05. Post-intervention HR and RRs were significantly lower in the mindfulness group relative to the no-intervention group (77.0 vs 120.1 bpm, respectively). Similar results were observed for RR (15.0 vs 23.6 breaths⋅min-1, respectively) and HRV indices (SDNN: 46.9 vs 33.1 ms and rMSSD: 17.9 vs 13.8 ms, respectively) Athletes in the rest group showed significantly lower post-intervention HR (-30.2 bpm, 89.9 vs 120.1 bpm, respectively), RR (-4.3 breaths⋅min-1, 19.3 vs 23.6 breaths⋅min-1, respectively) and significantly higher HRV (SDNN: 42.9 vs 33.1 ms and rMSSD: 16.7 vs 13.8 ms, respectively) compared to their no-intervention counterparts. Conclusions: Our findings suggest that athletes engaging in either 15-minute guided mindfulness or rest activities post training, may facilitate PNS reactivation.